Estudio de factibilidad en la elaboración de mortadela pizza en el taller de cárnicos ESPAM MFL - Mendoza Reyna, Silvia Verónica (2013)
This thesis aimed the feasibility analysis for the Preparation of Mortadella Pizza in the meat workshop of the ESPAM-MFL, Calceta City. The idea for this research comes from the sausage production increasingly moving in the market, and the ability to meet this challenge in terms of developing an innovative product for feeding families young or adults, who pay attention to the variety, flavor and texture. The proposal was to conduct a market analysis, that through survey and other tools allowed diagnose the demand and supply of the product and the competitive characteristics of the same, which gave enough information to make the respective decisions, determining the levels of acceptance of Mortadella Pizza within the Calceta population. The feasibility analysis was aimed on raw material costs in order to give the customer a better product cost and quality of their acceptance in accordance to their needs.